Power Distance Culture and Organizational Performance of Small and Medium Scale Enterprises in Bayelsa State - Tamunosiki-Amadi, Jasmine Okponanabofa; Diwerinepre, Ene Ezekiel (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
Abstract-This study examined Power Distance Culture and Organizational performance of small and medium scale enterprises in Bayelsa State. The study was necessitated by the fact that, SMEs are considered as engines for economic growth and development. Although, government has made significant effort in the establishment and development of the sector, there is still much to be desired in meeting and reaping the expected benefits. The study population consisted of officially registered SMEs in Bayelsa State, numbering 1450. The sample size of 313 respondents was selected using multi-stage sampling techniques. The internal reliability of the items was determined using Cronbach Alpha and reliability coefficient of 0.71 was obtained. Quantitative data were analyzed using statistical package for social sciences (SPSS). Descriptive and inferential statistics were used to describe and interpret the data. The research hypotheses were tested using Spearman Rank Order correlation coefficient (Rho). With 217 questionnaires that was retrieved out of 313 questionnaires distributed, findings were made and following conclusions drawn. The study shows that, there is positive relationship between power distance culture and the measures of performance. Therefore, the following recommendations were made: SMEs should put in place organizational structures. It recommends that rules and regulations should be put in place in organizations and decision making should be sole responsibility of management in order to enhance the performance of SMEs.